Evaluation of cashew apple RTS beverages blend with mango and papaya for its physicochemical properties and storage life - Kannan, S; Noorjehan, A K A H; Baskaran, A; Raja, N (Plant Science Today, 2025)
For every tonne of cashew nuts, 10 to 15 tonnes of cashew apples are spoiled in orchards, representing a significant economic loss in India. Cashew apple juice is astringent because of the presence of anacardic acid and tannins when eaten as such. Ready-to-serve (RTS) beverages prepared from cashew apple juice blended with mango and papaya in varying proportions were evaluated for physicochemical properties, organoleptic scores and microbial counts at 0, 30, 60, and 90 days of storage during 2022-2023 using Completely Randomized Design with two replications and six treatments. RTS blend of 50% cashew apple and 50% mango juice (T2) exhibited a gradual reduction in pH and ascorbic acid content and an increase in density, total soluble solids (TSS), acidity, reducing sugar and TSS/acid ratio from 0 to 90 days of storage followed by T6, a blend of 25% cashew apple and 75% papaya juice RTS. The RTS blends T2 and T6 had low microbiological counts and excellent quality, colour, taste, and general acceptance based on organoleptic score. The highest net benefit for an RTS beverage was in T3 (Rs. 32/-) followed by T2 (Rs. 27.25/-) when compared to control (100% cashew apple juice @Rs. 21/-). They also had affordable preparation costs, which added value to the cashew apple juice.